Constrained online trajectory planning for nonlinear flat SISO systems using a switched state variable filter. (December 2019) - Joos, Steffen; Bitzer, Matthias; Karrelmeyer, Roland; Graichen, Knut
Abstract: The problem of constrained Online Trajectory Planning (OTP) for Flatness-based Feedforward Controllers (FFC) is discussed for online tracking problems with a-priori unknown reference signals for the system output. As plant, nonlinear minimum phase Single Input Single Output (SISO) systems with input constraints as well as polytopic constraints on the flat state are assumed. The goal is to achieve both, fast reference tracking and a prioritization-based constraint satisfaction despite avoiding an online optimization. Therefore, the OTP is set up by means of a switched State Variable Filter (SSVF). The switching results from the limitation of the filter's highest derivative in accordance to the above requirements and is derived with a piecewise solution of an underlying optimization problem. The paper shows the derivation of the SSVF, discusses necessary stability conditions of the proposed concept, and finally demonstrates the SSVF's performance by means of a simulation study. A comparison to a respective optimal control problem solution and model predictive controller (MPC) is furthermore provided.